Evaluation of Total Antioxidant Capacity in Serum and Follicular Fluid of Women Undergoing ICSI and its Association with Implantation Failure (Medico Legal Update, 2020)
Purpose: Total antioxidant capacity (TAC) in women serum and follicular fluid (FF) which surroundingoocytes may be related to the implantation failure .Therefore, we herein examined the relationship betweentotal antioxidant capacity status in serum and FFand it is association with implantation failureMethod: One hundred and seventeen of non-reproductive women who underwent intra-cytoplasmic sperminjection (ICSI)included in this study and conducted between March 2018 and April 2019 in Kamal ALSamaraiHospital, center of fertility and IVF. Serum and follicular fluid were collected from non-reproductivewomen aged ranged 20-45 years and BMI (ranged 21.9-36.3kg/m2), TAC were measured using sandwichELISA in serum and follicular fluid specimen of 21 women of successful implantation compared to 96experienced implantation failures.Results: TAC was increased in serum of implantation failure compared to successful but not significantdifferences between two study groups. Whereas TAC levels were highly significant (P=0.002) inFFof women who had successful implantation (1.08 ± 0.64mmol/L) whereas in failure were lower(0.55 ±0.42 mmol/L). In addition to that, when evaluating the frequency of TAC category in FF revealed highlysignificant differences (P=0.003) between two groups, the majority of failure groups(84.4%) had low TACcompared with (40%) in successful groups, while a significant increase of sufficient TAC in successful thanfailure groups (50% versus 6.1% respectively), whereas the borderline TAC were (9.1% versus 10%) infailure and successful groups.Conclusions: TAC in FF may be potential markers for implantation successful in ICSI cycle.